Operabygningen i Oslo: et økologisk paradoks - Elin Haugdal (Nordlit: Tidsskrift i litteratur og kultur, 2011)
This essay discusses the Oslo Opera House building designed by Snøhetta (inaugurated 2008) as one of three monumental buildings in EU's Eco Culture Program and a so called demonstration building for ecological solutions in architecture. The most visible result in the Opera building is a large-scale glass wall with integrated solar cell panels, producing electricity as well as providing sun shading. The real ecological values, however, are hardly to be measured in money or watt, nor in reduced emissions or climatic change. This solar wall is first and foremost putting a strong ecological intention on display.